Process and energy intensification of glycerol carbonate production from glycerol and dimethyl carbonate in the presence of eggshell-derived cao heterogeneous catalyst - Praikaew, W. (MDPI AG, 2021)
The process and energy intensifications for the synthesis of glycerol carbonate (GC) from glycerol and dimethyl carbonate (DMC) using an eggshell-derived CaO heterogeneous catalyst were investigated. The transesterification reaction between glycerol and DMC was typically limited by mass transfer because of the immiscible nature of the reactants. By varying the stirring speed, it was observed that the mass transfer limitation could be neglected at 800 rpm. The presence of the CaO solid catalyst made the mass transport-limited reaction process more prominent. Mass transfer intensification using a simple kitchen countertop blender as an alternative to overcome the external mass transfer limitation of a typical magnetic stirrer was demonstrated. A lower amount of the catalyst and a shorter reaction time were required to achieve 93 glycerol conversion or 91 GC yield, and the turnover frequency (TOF) increased almost 5 times from 1.5 to 7.2 minâ1 when using a conventional magnetic stirrer and countertop blender, respectively. In addition, using a simple kitchen countertop blender with 7200 rpm, the reaction temperature of 60â¦C could be reached within approximately 3 min without the need of a heating unit. This was the result of the self-frictional heat generated by the high-shear blender. This was considered to be heat transfer intensification, as heat was generated locally (in situ), offering a higher homogeneity distribution. Meanwhile, the trend toward energy intensification was promising as the yield efficiency increased from 0.064 to 2.391 g/kJ. A comparison among other process intensification techniques, e.g., microwave reactor, ultrasonic reactor, and reactive distillation was also rationalized. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.